An interaction between congestion-control based transport protocols and MANET routing protocols - Mohd Zaini, Khuzairi; Habbal, Adib M. Monzer; Azzali, Fazli; Hassan, Suhaidi; Rizal, Mohamad (Science Publications, 2012)
Problem statement: Although many efforts have been done on studying the behaviour of TCP in MANET, but the behaviour of TFRC remain unclear in MANET. The purpose of this research is two folds.First, we studied the behaviour of TFRC and TCP over AODV and DSR as the underlying routing protocols in terms of throughput, delay and jitter.The second objective was to identify whether MANET routing protocols have an impact on transport protocols or not.Approach: Network Simulator 2 (NS-2) was used to conduct all of the experiments, i.e., TFRC over AODV, TFRC over DSR, TCP over AODV and TCP over DSR.We created 30 nodes on a 1000×1000 m location area and each node was assigned CBR traffic, transport protocol and routing protocol.In order to simulate the nodes mobility, we implemented a Random Waypoint mobility model with varying speeds of 5, 10, 15 and 20 m sec−1 (m/sec) with a 10 sec pause time.Results: We observed that TFRC throughput increases almost 55% when using DSR as its routing protocol, but TCP throughput has no significant difference with different underlying protocols.However, in terms of jitter and delay, both routing protocols, i.e., AODV and DSR have the impact of more than 50% on TFRC and TCP. Conclusion/Recommendations: The results obtained also show us that TFRC or TCP should choose AODV as its routing protocol because it has less jitter which is one of the critical performance metrics for multimedia applications.